Artificial tastes better? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Vanilla is the most highly consumed spice in the world (2,000 tonnes a year), and it also suffers from the strongest competition from synthetic extracts. They are so much cheaper that they now account for more than nine-tenths of the market for...